Identification of rodent species confirmed as the cause of leptospirosis disease with ecosystem distribution and environmental factors - Komalaningsih, Sri; Juliansyah, Ryan (Journal of Character and Environment, 2024)
Background: Leptospirosis outbreaks have been reported in various parts of the world, classifying it as a re-emerging infectious disease. Rats act as the main reservoir for Leptospira spp. bacteria. The Indonesian Ministry of Health reported 1,170 cases of leptospirosis with 106 deaths Case Fatality Rate (CFR 9.1%) in 2020, obtained from 8 provinces. Additionally, in 2021, there was a decrease in cases by 734, but with an increased CFR of 11.4%, with the largest contributors being Central Java and East Java. Objective: To determine the most dominant rodent species confirmed to cause leptospirosis and the distribution of ecosystems and environmental factors that are the dominant causes of leptospirosis. Methods: This paper is a narrative literature review study. Articles were searched through online databases such as Google Scholar and PubMed using keywords leptospirosis, rats, ecosystem, and environmental factors, published within the last 5 years. Findings: The identification results showed that Bandicota indica was the most dominant rodent species infected with leptospirosis. This type of rat is a commensal species. Leptospirosis cases occurred in non-forest ecosystems near settlements and coastal areas near settlements. The dominant environmental factors associated with leptospirosis incidence were poor sanitation conditions, indiscriminate waste disposal behavior, and stagnant water. Conclusion: The identification results indicate that Bandicota indica is the most dominant rodent species infected with leptospirosis, being a commensal rat species in non-forest ecosystems near settlements and coastal areas near settlements. The dominant environmental factors associated with leptospirosis incidence include poor sanitation conditions, indiscriminate waste disposal behavior, and stagnant water. Novelty/Originality of this Study: The study's findings confirmed that non-forest and coastal ecosystems near settlements are significant reservoirs for Leptospira bacteria. Additionally, it highlighted the critical role of poor sanitation, indiscriminate waste disposal, and stagnant water as environmental factors contributing to the transmission of leptospirosis.